Computational study of the atomic structure of grain boundaries in solid oxides - Lindman, Anders (My University, 2011)
BaZrO3 is a perovskite oxide that is a good candidate for an intermediate temperature proton conductor in SOFC, because it is chemically stable and has high bulk proton conductivity. However, the total conductivity of the material is low due to high proton resistance at the grain boundaries. Theories suggest that this is caused by oxygen vacancy migration to these boundaries. The aim of this project was to study oxygen vacancy segregation in [¯110] symmetric tilt grain boundaries of BaZrO3. A semi-empirical interatomic potential has been used to study the boundaries since first-principles simulations are too computationally heavy for most of them. A study of two simple grain boundaries was conducted with both methods to determine the transferability of the potential. The study suggested that the semiempirical approach predicts the structure and energy of the boundaries in a reasonably accurate manner. The structures of eight different grain boundaries with reasonable grain boundary energy were found using the interatomic potential. The oxygen vacancy segregation of these boundaries was then investigated. The results showed that the preferred vacancy positions were close to the boundary planes for each grain boundary and the minimum segregation energies were in the range [-1.86,-0.83]eV, which suggests that oxygen vacancy migration to the boundaries will occur. Polarizability was also introduced to the simulations through use of the shell model. These simulations predicted different energies but similar structures, and the same segregation ordering as the simulations without polarizability.
Keywords: Energi; Hållbar utveckling; Nanovetenskap och nanoteknik; Fysik; Energy; Sustainable Development; Nanoscience & Nanotechnology; Physical Sciences